Pharmaceutical assessment of the rationale of the application of chemotherapy schemes containing immunotherapeutic drugs in the treatment of classical Hodgkin's lymphoma - M. R. Matushchak; H. L. Panfilova (The State Expert Center of the Ministry of Health of Ukraine, 2023)
The use of new chemotherapy regimens for Hodgkin lymphoma, containing immunotherapeutic drugs, such as brentuximab vedotin, is an urgent direction in the development of modern oncohematology. The inclusion of these drugs in programs of financial support for hematological oncology patients by the state requires an assessment of the rationality of their use under the conditions of the current health care resource provision. The aim of the research is to carry out a pharmacoeconomic evaluation of the rationality of the use of brentuximab vedotin drugs in the treatment of classic Hodgkin lymphoma. Materials - the results of clinical studies of the effectiveness of two chemotherapy regimens for Hodgkin lymphoma (BrECAPP and BrECADD), which were published by German scientists in 2017 (Cochrane Central Register of Controlled Trials, CN-01443068), data from the domestic market of anticancer drugs and state procurement of medicines. General theoretical and applied (organizational and economic, marketing and pharmacoeconomic analysis, mathematical and statistical, etc.) research methods were applied. According to the results of the pharmacoeconomic evaluation of the rationality of the use of the BrECAPP and BrECADD schemes in the treatment of Hodgkin lymphoma, it was established that according to the indices of complete response after chemotherapy (%) the BrECADD scheme has clinical and economic advantages of application, and according to the index of complete remission as the final result of treatment (%), the situation is quite the opposite, that is, the BrECAPP scheme has advantages. The evaluation of the safety profile of the application makes it possible to assert the advantages of the application of the BrECADD scheme. Thus, taking into account the three indices under study (organ toxicity (%), manifestations of peripheral neuropathies (%) and the development of hematological side effects (%)), the indicated scheme had a clinical and economic advantage over the alternative scheme in two indices. This is organ toxicity (%), CEA2 = UAH 3,323.87/unit. ef. (%) against CEA1 = UAH 3,854.52/unit. ef. (%) according to the BrECAPP scheme and the development of hematological side effects (%) - CEA2 = UAH 29,008.32/unit. ef. (%) against CEA1 = UAH 29,084.14/unit. ef. (%) according to the BrECAPP scheme. In general, it can be stated that the BrECADD scheme is more rational and has economic advantages in the treatment of classical Hodgkin lymphoma compared to the BrECAPP regimen in terms of clinical efficacy and safety profile.